Method for preventing cathode of lithium carbon fluoride battery from being corroded

By using a mixed solvent of specific ratios in the electrolyte of lithium fluorinated carbon batteries, the negative electrode corrosion and performance degradation caused by free fluorine in lithium fluorinated carbon batteries are solved, and the storage stability and safety of the battery are improved.

CN119695273APending Publication Date: 2025-03-25EVE ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411824341.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The presence of unreacted free fluorine in lithium fluoride carbon batteries leads to corrosion on the surface of lithium negative electrode, increased internal resistance and reduced battery performance, especially under high temperature conditions.

Method used

By using mixed solvents in the electrolyte of lithium fluorinated carbon batteries, including the first solvent (such as propylene carbonate, gamma-butyrolactone, etc.) and the second solvent (such as ethylene glycol dimethyl ether, tetrahydrofuran, etc.), the ratio is adjusted to control the free fluorine concentration and hydrofluoric acid concentration in the electrolyte, thereby inhibiting the generation of free fluorine and the destruction of fluorine-carbon bonds.

Benefits of technology

It effectively suppresses corrosion of the negative electrode of lithium fluoride carbon battery, reduces internal resistance, improves the storage stability and safety of the battery, and avoids performance degradation in cell expansion and high-temperature storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695273A_ABST
    Figure CN119695273A_ABST
Patent Text Reader

Abstract

The invention specifically discloses a method for preventing a lithium carbon fluoride battery negative electrode from being corroded. The invention relates to a method for preventing corrosion of a negative electrode of a lithium carbon fluoride battery, which comprises the following steps: preparing the lithium carbon fluoride battery by using an electrolyte containing a first solvent and a second solvent in a formula, and controlling the ratio of the first solvent to the second solvent so that the volume ratio of the second solvent in a mixed solvent is less than 50%; wherein the first solvent comprises at least one of propylene carbonate, gamma-butyrolactone, ethylene carbonate, butylene carbonate and diethyl carbonate; the second solvent comprises at least one of ethylene glycol dimethyl ether, tetrahydrofuran, dimethyl carbonate and methyl ethyl carbonate. The electrolyte has the advantages that the content of free fluorine in the electrolyte for the lithium carbon fluoride battery is reduced, so that the storage stability and the use safety of the lithium carbon fluoride battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to a method for preventing corrosion of the negative electrode of a lithium carbon fluoride battery. Background Art

[0002] Lithium carbon fluoride (Li-CFx) batteries have high specific energy (1560W.h / kg), higher voltage platform (2.4V), longer storage life (can be stored for 10 years at room temperature with self-discharge rate ≤1%), reliability and wide temperature range (-40℃ to 170℃). Therefore, they have attracted much attention in the fields of medical equipment, military industry, aerospace, etc. and have broad application prospects.

[0003] Carbon fluoride is currently generally prepared by reacting carbon materials such as natural / artificial graphite with fluorine gas. However, there is unreacted fluorine in the carbon fluoride prepared at present. These unreacted fluorine exist in a free state and are not bound to carbon atoms, which will have various effects on the material properties. For example, in lithium carbon fluoride batteries using carbon fluoride as the positive electrode active material, carbon fluoride containing a large amount of non-bonded fluorine will cause corrosion on the surface of the lithium negative electrode and increase the internal resistance, thereby reducing the performance of the lithium carbon fluoride battery. Especially under high temperature conditions, the dissolution of free fluorine in the carbon fluoride active material will seriously affect the discharge performance of the lithium carbon fluoride battery. Not only that, it will also cause the battery cell to swell or even leak; in addition, a large amount of non-bonded fluorine may cause the initial discharge voltage to rise sharply, thereby causing damage to the circuit, etc.

[0004] Therefore, inhibiting free fluorine in carbon fluoride is an important issue in the development of lithium carbon fluoride system batteries. Usually, in order to improve the stability of carbon fluoride materials, carbon fluoride materials are generally purified or a coating is formed on their surface to reduce the concentration of free fluorine, but the operation of purifying carbon fluoride and coating carbon fluoride is relatively complicated and not easy to mass produce. This patent provides a simple and feasible electrolyte control method to inhibit the generation of free fluorine, so as to improve the storage stability and safety of lithium carbon fluoride batteries. Summary of the invention

[0005] In order to reduce the content of free fluorine in the electrolyte for lithium carbon fluoride batteries to improve the storage stability and use safety of lithium carbon fluoride batteries, the present application provides a method for preventing corrosion of the negative electrode of lithium carbon fluoride batteries.

[0006] In the first aspect, the present application provides a method for preventing corrosion of the negative electrode of a lithium fluoride carbon battery, which adopts the following technical solution:

[0007] A method for preventing negative electrode corrosion of a lithium fluoride carbon battery, comprising preparing a lithium fluoride carbon battery using an electrolyte containing a mixed solvent in the formula; the mixed solvent comprises a first solvent and a second solvent, and the ratio of the first solvent to the second solvent is controlled so that the volume proportion of the second solvent in the mixed solvent is less than 50%, for example, 1%, 5%, 10%, 20%, 25%, 30%, 35%, 40%, 49%, but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable;

[0008] Wherein, the first solvent includes at least one of propylene carbonate (PC), γ-butyrolactone (γ-GBL), ethylene carbonate (EC), butylene carbonate (BC), and diethyl carbonate (DEC);

[0009] The second solvent includes at least one of ethylene glycol dimethyl ether (DME), tetrahydrofuran (THF), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC).

[0010] In the prior art, ethylene glycol dimethyl ether (DME) is often used in the electrolyte for lithium carbon fluoride batteries to achieve the effect of stabilizing the metallic lithium negative electrode. However, when the electrolyte containing ethylene glycol dimethyl ether (DME) is specifically applied, it is found that the impedance of the lithium carbon fluoride battery still increases after storage. In severe cases, the battery cell even swells, which has an adverse effect on the storage safety of the lithium carbon fluoride battery.

[0011] The present application prepares an electrolyte for a lithium fluorinated carbon battery by using a first solvent and a second solvent and adjusting the ratio of the first solvent to the second solvent, so as to obtain an electrolyte with high ionic conductivity, wide electrochemical stability window, good thermal stability, stable chemical properties, and safe and low toxicity, which helps to improve the storage stability of the lithium fluorinated carbon battery; at the same time, the present application adjusts the volume ratio of the second solvent in the electrolyte for a lithium fluorinated carbon battery. On the one hand, the free fluorine in the electrolyte can form a uniformly distributed fluorine-containing interface layer at the negative electrode interface under the action of the second solvent, which helps to improve the electrochemical stability of the lithium fluorinated carbon battery; on the other hand, the combination of the first solvent and the second solvent can also reduce the destructive effect of the second solvent on unstable fluorine-carbon bonds during long-term high-temperature storage, thereby reducing the generation of free fluorine, and then avoiding the generation of uneven and thick LiF shells at the lithium metal negative electrode interface, which helps to keep the lithium fluorinated carbon battery at a low impedance level, improve the capacity retention rate of the lithium fluorinated carbon battery, and avoid cell expansion and improve the safety of the lithium fluorinated carbon battery.

[0012] Preferably, by adjusting the ratio of the first solvent and the second solvent, the free fluorine concentration of the positive electrode material in the lithium fluoride carbon battery in the electrolyte is controlled to be 50-500ppm, for example, it can be 50ppm, 100ppm, 150ppm, 180ppm, 250ppm, 350ppm, 400ppm, 450ppm, 500ppm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0013] Preferably, by adjusting the ratio of the first solvent and the second solvent, the free fluorine concentration of the positive electrode material in the lithium fluoride carbon battery in the electrolyte is controlled to be 150-250ppm, for example, it can be 150ppm, 160ppm, 190ppm, 210ppm, 230ppm, 240ppm, 250ppm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] Preferably, the volume ratio of the first solvent to the second solvent is 1.5-2:1, for example, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] The present application further optimizes the ratio of the first solvent to the second solvent in the electrolyte for lithium carbon fluoride batteries. On the one hand, it can further improve the stability of the electrolyte, reduce the free fluorine concentration of the positive electrode material in the electrolyte, and maintain the hydrofluoric acid in the electrolyte at an appropriate concentration; on the other hand, it helps to reduce the possibility of fluorine-carbon bond breakage in the carbon fluoride material, avoid further increase in free fluorine concentration, improve deposition uniformity at the lithium metal negative electrode interface, and help improve the capacity retention rate and safety of the lithium carbon fluoride battery after storage.

[0016] Preferably, by adjusting the ratio of the first solvent and the second solvent, the concentration of hydrofluoric acid in the electrolyte is controlled to be 1-10ppm, for example, it can be 1ppm, 3ppm, 5ppm, 7ppm, 8ppm, 9ppm, 10ppm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] In the present application, by selecting a suitable first solvent and a second solvent and adjusting the ratio of the first solvent to the second solvent, the concentration of hydrofluoric acid in the electrolyte can be controlled within the above range, thereby reducing the negative impact of hydrofluoric acid on the SEI film at the interface of the lithium metal negative electrode, which helps to improve the high-temperature storage stability of the lithium fluoride carbon battery.

[0018] Preferably, the electrolyte also includes a lithium salt, and the concentration of the lithium salt in the electrolyte is 0.5-2 mol / L, for example, 0.5 mol / L, 0.8 mol / L, 1.1 mol / L, 1.3 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] In the present application, by controlling the lithium salt concentration to be within the above range, the generation of a solvation structure in the electrolyte can be avoided, the structure and chemical composition of the interface film will not be affected, and the storage stability of the lithium fluoride carbon battery can be improved.

[0020] Preferably, the lithium salt comprises lithium hexafluorophosphate (LiPF 6 ), lithium bis(oxalatoborate) (LiBOB), lithium tetrafluoroborate (LiBF 4 ), lithium difluorooxalatoborate (LiODFB), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO2F2), and lithium tetrafluorooxalatophosphate (LiFOP).

[0021] Preferably, the conductivity of the electrolyte is 9-12 mS / cm, for example, 9 mS / cm, 10 mS / cm, 10.5 mS / cm, 11 mS / cm, 11.5 mS / cm, 12 mS / cm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] Preferably, the conductivity of the electrolyte at 20° C. is 9-12 mS / cm.

[0023] By limiting the conductivity in the electrolyte to be maintained within the above range, the migration rate of ions in the electrolyte can be maintained at a faster level, which helps to form a stable and uniform SEI film, thereby improving the protection effect on the lithium metal negative electrode interface and helping to improve the capacity retention rate of the lithium fluoride carbon battery after storage; in addition, it also helps the lithium fluoride carbon battery to dissipate heat, improves its heat dissipation performance during high-temperature storage, and helps to improve the storage safety of the lithium fluoride carbon battery.

[0024] Preferably, the second solvent comprises ethylene glycol dimethyl ether.

[0025] In the second aspect, the present application provides a lithium carbon fluoride battery, which adopts the following technical solution:

[0026] A lithium fluoride carbon battery comprises an electrolyte, wherein the electrolyte comprises a mixed solvent, the mixed solvent comprises a first solvent and a second solvent, the volume proportion of the second solvent in the mixed solvent is less than 50%; the first solvent comprises at least one of propylene carbonate, γ-butyrolactone, ethylene carbonate, butylene carbonate, and diethyl carbonate; the second solvent comprises at least one of ethylene glycol dimethyl ether, tetrahydrofuran, dimethyl carbonate, and ethyl methyl carbonate. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 For Example 1 ( Figure 1 a), Comparative Examples 1-2 ( Figure 1 b-1c) Diagram of the disassembled interface of the negative electrode of the lithium carbon fluoride battery. DETAILED DESCRIPTION

[0028] For better understanding and implementation, the technical solution of the present application will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0030] Unless otherwise indicated, all numerical values ​​expressing quantities of ingredients, reaction conditions, and so forth used in the specification and claims are to be understood as modified by the term “about.” Accordingly, unless indicated to the contrary, the numerical parameters set forth herein are approximations that can vary depending upon the desired properties desired to be obtained.

[0031] As used herein, "and / or" means one or all of the mentioned elements.

[0032] As used herein, “including” and “comprising” encompasses the case where only the stated elements are present as well as the case where there are other elements other than the stated elements.

[0033] All percentages in this application are by weight unless otherwise stated.

[0034] Unless otherwise indicated, "a", "an", "an" and "the" used in this specification are intended to include "at least one" or "one or more". For example, "a component" means one or more components, so more than one component may be considered and may be employed or used in the implementation of the embodiment.

[0035] Example 1

[0036] 1. Preparation of positive electrode

[0037] Graphite fluoride, conductive agent (Super-P), and binder (polyvinylidene fluoride PVDF) were mixed evenly in a mass ratio of 87:8:5, coated on pure aluminum foil, dried at 55°C, and cut into pieces to obtain positive electrode sheets.

[0038] 2. Negative electrode preparation

[0039] A metallic lithium sheet is used as the negative electrode.

[0040] 3. Preparation of Electrolyte

[0041] In a glove box filled with argon, propylene carbonate (PC) and ethylene glycol dimethyl ether (DME) were prepared in a volume ratio of 2:1 to obtain a mixed solvent, and lithium salt lithium tetrafluoroborate (lithium salt concentration was 1 mol / L) was added to the mixed solvent to obtain an electrolyte for a lithium fluoride carbon battery (the free fluorine concentration of the positive electrode material in the lithium fluoride carbon battery in the electrolyte was 200 ppm, the hydrofluoric acid concentration in the electrolyte was 4.6 ppm, and the conductivity of the electrolyte was 9.6 mS / cm).

[0042] 4. Lithium Carbon Fluoride Battery Preparation

[0043] In a glove box filled with high-purity argon, a battery is assembled in the order of negative electrode shell, spring sheet, gasket, metal lithium sheet, alumina diaphragm, the above-prepared lithium fluoride carbon battery electrolyte, graphite fluoride positive electrode sheet, and positive electrode shell.

[0044] Example 2

[0045] 1. Preparation of positive electrode

[0046] Graphite fluoride, conductive agent (Super-P), and binder (polyvinylidene fluoride PVDF) were mixed evenly in a mass ratio of 87:8:5, coated on pure aluminum foil, dried at 55°C, and cut into pieces to obtain positive electrode sheets.

[0047] 2. Negative electrode preparation

[0048] A metallic lithium sheet is used as the negative electrode.

[0049] 3. Preparation of Electrolyte

[0050] In a glove box filled with argon, propylene carbonate (PC) and ethylene glycol dimethyl ether (DME) were prepared in a volume ratio of 1.5:1 to obtain a mixed solvent, and lithium salt lithium tetrafluoroborate (lithium salt concentration was 1 mol / L) was added to the mixed solvent to obtain an electrolyte for a lithium fluoride carbon battery (the free fluorine concentration of the positive electrode material in the lithium fluoride carbon battery in the electrolyte was 200 ppm, the hydrofluoric acid concentration in the electrolyte was 4.6 ppm, and the conductivity of the electrolyte was 9.6 mS / cm).

[0051] 4. Lithium Carbon Fluoride Battery Preparation

[0052] In a glove box filled with high-purity argon, a battery is assembled in the order of negative electrode shell, spring sheet, gasket, metal lithium sheet, alumina diaphragm, the above-prepared lithium fluoride carbon battery electrolyte, graphite fluoride positive electrode sheet, and positive electrode shell.

[0053] Example 3

[0054] 1. Preparation of positive electrode

[0055] Graphite fluoride, conductive agent (Super-P), and binder (polyvinylidene fluoride PVDF) were mixed evenly in a mass ratio of 87:8:5, coated on pure aluminum foil, dried at 55°C, and cut into pieces to obtain positive electrode sheets.

[0056] 2. Negative electrode preparation

[0057] A metallic lithium sheet is used as the negative electrode sheet.

[0058] 3. Preparation of Electrolyte

[0059] In a glove box filled with argon, γ-butyrolactone (γ-GBL) and ethylene glycol dimethyl ether (DME) were prepared in a volume ratio of 2:1 to obtain a mixed solvent, and lithium salt lithium tetrafluoroborate (lithium salt concentration was 1.5 mol / L) was added to the mixed solvent to obtain an electrolyte for a lithium fluoride carbon battery (the free fluorine concentration of the positive electrode material in the lithium fluoride carbon battery in the electrolyte was 400 ppm, the hydrofluoric acid concentration in the electrolyte was 6.5 ppm, and the conductivity of the electrolyte was 11.2 mS / cm).

[0060] 4. Lithium Carbon Fluoride Battery Preparation

[0061] In a glove box filled with high-purity argon, a battery is assembled in the order of negative electrode shell, spring sheet, gasket, metal lithium sheet, alumina diaphragm, the above-prepared lithium fluoride carbon battery electrolyte, graphite fluoride positive electrode sheet, and positive electrode shell.

[0062] Example 4

[0063] 1. Preparation of positive electrode

[0064] Graphite fluoride, conductive agent (Super-P), and binder (polyvinylidene fluoride PVDF) were mixed evenly in a mass ratio of 87:8:5, coated on pure aluminum foil, dried at 55°C, and cut into pieces to obtain positive electrode sheets.

[0065] 2. Negative electrode preparation

[0066] A metallic lithium sheet is used as the negative electrode sheet.

[0067] 3. Preparation of Electrolyte

[0068] In a glove box filled with argon, propylene carbonate (PC) and dimethyl carbonate (DMC) were prepared in a volume ratio of 2:1 to obtain a mixed solvent, and lithium salt lithium tetrafluoroborate (lithium salt concentration was 1 mol / L) was added to the mixed solvent to obtain an electrolyte for a lithium fluoride carbon battery (the free fluorine concentration of the positive electrode material in the lithium fluoride carbon battery in the electrolyte was 100 ppm, the hydrofluoric acid concentration in the electrolyte was 2.6 ppm, and the conductivity of the electrolyte was 9.6 mS / cm).

[0069] 4. Lithium Carbon Fluoride Battery Preparation

[0070] In a glove box filled with high-purity argon, a battery is assembled in the order of negative electrode shell, spring sheet, gasket, metal lithium sheet, alumina diaphragm, the above-prepared lithium fluoride carbon battery electrolyte, graphite fluoride positive electrode sheet, and positive electrode shell.

[0071] Example 5

[0072] 1. Preparation of positive electrode

[0073] Graphite fluoride, conductive agent (Super-P), and binder (polyvinylidene fluoride PVDF) were mixed evenly in a mass ratio of 87:8:5, coated on pure aluminum foil, dried at 55°C, and cut into pieces to obtain positive electrode sheets.

[0074] 2. Negative electrode preparation

[0075] A metallic lithium sheet is used as the negative electrode sheet.

[0076] 3. Preparation of Electrolyte

[0077] In a glove box filled with argon, ethylene carbonate (EC) and dimethyl carbonate (DMC) were prepared in a volume ratio of 1.5:1 to obtain a mixed solvent, and lithium salt lithium tetrafluoroborate (lithium salt concentration was 1 mol / L) was added to the mixed solvent to obtain an electrolyte for a lithium fluoride carbon battery (the free fluorine concentration of the positive electrode material in the lithium fluoride carbon battery in the electrolyte was 55 ppm, the hydrofluoric acid concentration in the electrolyte was 1.8 ppm, and the conductivity of the electrolyte was 10.4 mS / cm).

[0078] 4. Lithium Carbon Fluoride Battery Preparation

[0079] In a glove box filled with high-purity argon, a battery is assembled in the order of negative electrode shell, spring sheet, gasket, metal lithium sheet, alumina diaphragm, the above-prepared lithium fluoride carbon battery electrolyte, graphite fluoride positive electrode sheet, and positive electrode shell.

[0080] Example 6

[0081] 1. Preparation of positive electrode

[0082] Graphite fluoride, conductive agent (Super-P), and binder (polyvinylidene fluoride PVDF) were mixed evenly in a mass ratio of 87:8:5, coated on pure aluminum foil, dried at 55°C, and cut into pieces to obtain positive electrode sheets.

[0083] 2. Negative electrode preparation

[0084] A metallic lithium sheet is used as the negative electrode.

[0085] 3. Preparation of Electrolyte

[0086] In a glove box filled with argon, propylene carbonate (PC) and ethylene glycol dimethyl ether (DME) were prepared in a volume ratio of 2:1 to obtain a mixed solvent, and lithium salt lithium tetrafluoroborate (lithium salt concentration was 1 mol / L) was added to the mixed solvent to obtain an electrolyte for a lithium fluoride carbon battery (the free fluorine concentration of the positive electrode material in the lithium fluoride carbon battery in the electrolyte was 520 ppm, the hydrofluoric acid concentration in the electrolyte was 10.5 ppm, and the conductivity of the electrolyte was 10.4 mS / cm).

[0087] 4. Lithium Carbon Fluoride Battery Preparation

[0088] In a glove box filled with high-purity argon, a battery is assembled in the order of negative electrode shell, spring sheet, gasket, metal lithium sheet, alumina diaphragm, the above-prepared lithium fluoride carbon battery electrolyte, graphite fluoride positive electrode sheet, and positive electrode shell.

[0089] Comparative Example 1

[0090] The difference between this comparative example and Example 1 is that the volume ratio of the first solvent to the second solvent is 1:1; the remaining steps and parameter settings are consistent with Example 1.

[0091] Comparative Example 2

[0092] The difference between this comparative example and Example 1 is that the volume ratio of the first solvent to the second solvent is 1:2; the remaining steps and parameter settings are consistent with Example 1.

[0093] Comparative Example 3

[0094] The difference between this comparative example and Example 3 is that the volume ratio of the first solvent to the second solvent is 1:2; the remaining steps and parameter settings are consistent with Example 3.

[0095] Comparative Example 4

[0096] The difference between this comparative example and Example 4 is that the volume ratio of the first solvent to the second solvent is 1:2; the remaining steps and parameter settings are consistent with Example 4.

[0097] Comparative Example 5

[0098] The difference between this comparative example and Example 5 is that the volume ratio of the first solvent to the second solvent is 1:2; the remaining steps and parameter settings are consistent with Example 5.

[0099] Test Method

[0100] 1. Storage stability test of lithium carbon fluoride battery

[0101] The storage stability test of the lithium carbon fluoride batteries in the above embodiments and comparative examples is carried out, and the specific test method is as follows: (1) At room temperature, the lithium / carbon fluoride battery is discharged at 0.01C, and the discharge cut-off voltage is 2.0V, and the discharge capacity of the new battery, the initial thickness H1 of the battery cell and the internal resistance R1 are recorded; (2) After the new lithium carbon fluoride battery of the same type is placed in a 60°C oven and stored for 100 days, it is tested again under the above conditions and the discharge capacity of the battery after high temperature storage, the thickness H2 of the battery cell after storage and the internal resistance R2 are recorded;

[0102] Discharge capacity retention rate = discharge capacity of battery after high temperature storage / discharge capacity of new battery × 100%;

[0103] Internal resistance growth rate = (internal resistance R2 after storage - internal resistance R1 before storage) / internal resistance R1 before storage × 100%;

[0104] Thickness expansion rate = (cell thickness after storage H2 - cell initial thickness H1) / cell initial thickness H1 × 100%;

[0105] In addition, the interface of the lithium metal negative electrode after storage in Example 1 and Comparative Example 1-2 was disassembled, and the interface conditions were as follows: Figure 1 shown.

[0106] Table 1

[0107] Serial number Internal resistance growth rate / % Thickness expansion rate / % Discharge capacity retention rate / % Example 1 40.3 0.1 98.94 Example 2 39.1 0.1 98.98 Example 3 38.8 0.2 99.03 Example 4 41.8 0.05 98.93 Example 5 42.9 0.3 98.65 Example 6 44.2 0.4 98.01 Comparative Example 1 45.3 0.6 96.08 Comparative Example 2 204.3 8.3 79.92 Comparative Example 3 211.9 7.9 81.73 Comparative Example 4 295.8 9.0 77.93 Comparative Example 5 235.9 7.9 80.83

[0108] In combination with Examples 1-6, Comparative Examples 1-5 and Table 1, it can be seen that the present application uses a mixed solvent formed by a first solvent and a second solvent, and adjusts the volume proportion of the second solvent in the mixed solvent in the electrolyte to less than 50%, which can not only form a uniform SEI film at the negative electrode lithium metal interface of the lithium fluoride carbon battery, but also improve the stability of the fluorine-carbon bond of the lithium fluoride carbon battery during high-temperature storage, reduce the concentration of free fluorine, and further improve the negative electrode interface stability, so that the lithium fluoride carbon battery can maintain a low impedance level during long-term storage, so that the lithium fluoride carbon can maintain a low internal resistance growth rate, thickness expansion rate and high discharge capacity retention rate; when the proportion of the second additive in the mixed solvent is greater than or equal to 50% (Comparative Example 1), there is a risk of corrosion of lithium metal, and when the proportion of the second additive in the mixed solvent is greater than 66.7% (Comparative Examples 2-5), the corrosion of lithium metal is more serious.

[0109] In combination with Examples 1 and 6 and Table 1, it can be seen that when the initial free fluorine concentration of the carbon fluoride material in the electrolyte is too high, even if the ratio of the first solvent to the second solvent in the electrolyte remains unchanged, the negative electrode lithium metal interface in the lithium carbon fluoride battery will also be at risk of corrosion. At this time, the internal resistance growth rate and thickness expansion rate of the lithium carbon fluoride battery increase, and the discharge capacity retention rate decreases.

[0110] Combining Examples 1, 3-5 and Table 1, it can be seen that changing the types of the first solvent (γ-butyrolactone γ-GBL, ethylene carbonate EC) and the second solvent presents the same results, that is, the internal resistance growth rate and thickness expansion rate of the lithium fluorinated carbon battery are small, while the discharge capacity retention rate remains at a high level.

[0111] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solution of the present application can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present application.

Claims

1. A method for preventing corrosion of the negative electrode of a lithium fluoride carbon battery, characterized in that: A lithium fluoride carbon battery is prepared using an electrolyte containing a mixed solvent in the formula; the mixed solvent includes a first solvent and a second solvent, and the ratio of the first solvent to the second solvent is controlled so that the volume proportion of the second solvent in the mixed solvent is less than 50%; Wherein, the first solvent comprises at least one of propylene carbonate, γ-butyrolactone, ethylene carbonate, butylene carbonate, and diethyl carbonate; The second solvent includes at least one of ethylene glycol dimethyl ether, tetrahydrofuran, dimethyl carbonate, and ethyl methyl carbonate.

2. The method for preventing corrosion of the negative electrode of a lithium fluoride carbon battery according to claim 1, characterized in that: By adjusting the ratio of the first solvent and the second solvent, the free fluorine concentration of the positive electrode material in the lithium carbon fluoride battery in the electrolyte is controlled to be 50-500 ppm.

3. The method for preventing the negative electrode of a lithium fluoride carbon battery from corroding according to claim 2, characterized in that: By adjusting the ratio of the first solvent and the second solvent, the free fluorine concentration of the positive electrode material in the lithium carbon fluoride battery in the electrolyte is controlled to be 150-250 ppm.

4. The method for preventing corrosion of the negative electrode of a lithium fluoride carbon battery according to claim 1, characterized in that: The volume ratio of the first solvent to the second solvent is 1.5-2:

1.

5. The method for preventing corrosion of the negative electrode of a lithium fluoride carbon battery according to claim 1, characterized in that: The concentration of hydrofluoric acid in the electrolyte is controlled within a range of 1-10 ppm by adjusting the ratio of the first solvent to the second solvent.

6. The method for preventing corrosion of the negative electrode of a lithium fluoride carbon battery according to claim 1, characterized in that: The electrolyte also includes lithium salt, and the concentration of the lithium salt in the electrolyte is 0.5-2 mol / L.

7. The method for preventing corrosion of the negative electrode of a lithium fluoride carbon battery according to claim 6, characterized in that: The lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, and lithium tetrafluorooxalatophosphate.

8. The method for preventing corrosion of the negative electrode of a lithium fluoride carbon battery according to claim 1, characterized in that: The conductivity of the electrolyte is 9-12 mS / cm.

9. The method for preventing negative electrode corrosion of a lithium fluoride carbon battery according to any one of claims 1 to 8, characterized in that: The second solvent includes ethylene glycol dimethyl ether.

10. A lithium carbon fluoride battery, characterized in that: An electrolyte is included, wherein the electrolyte includes a mixed solvent, the mixed solvent includes a first solvent and a second solvent, and the volume proportion of the second solvent in the mixed solvent is less than 50%; The first solvent includes at least one of propylene carbonate, γ-butyrolactone, ethylene carbonate, butylene carbonate, and diethyl carbonate; The second solvent includes at least one of ethylene glycol dimethyl ether, tetrahydrofuran, dimethyl carbonate, and ethyl methyl carbonate.